2011
DOI: 10.1002/acp.1792
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive Interview for Use with Adults: An Empirical Test of an Alternative Mnemonic and of a Partial Protocol

Abstract: Research showed that the four Cognitive Interview (CI) mnemonics used individually are unequally effective. We propose to test (i) their benefit when used within the same free recall phase and (ii) an original instruction, 'guided peripheral focus' (GPF). In two studies, 84 and 42 students were interviewed with Structured Interviews (SI), CIs or CI variations about a film viewed 1 week before. Results indicated that (i) if a CI variation with the GPF instead of the 'perspective' elicits more correct informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 31 publications
3
26
0
2
Order By: Relevance
“…The Modified Cognitive Interview produces more information than alternatives in the field First, the benefits of an MCI including 10 categories of social components from the interview framework defined by the ECI (i.e., SI) plus three mnemonics (i.e., report everything, mental context reinstatement, and sequenced and focused recall) were confirmed with real crime interviews, which extends what was previously observed in laboratory research (Colomb & Ginet, 2012). Then, in line with Geiselman et al (1984) and George and Clifford (1996), training professionals in the retrieval mnemonics improved the resulting interviews in the current experiment, which extends the benefit of the MCI to French-language countries and to military police forces practicing within inquisitor justice systems.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The Modified Cognitive Interview produces more information than alternatives in the field First, the benefits of an MCI including 10 categories of social components from the interview framework defined by the ECI (i.e., SI) plus three mnemonics (i.e., report everything, mental context reinstatement, and sequenced and focused recall) were confirmed with real crime interviews, which extends what was previously observed in laboratory research (Colomb & Ginet, 2012). Then, in line with Geiselman et al (1984) and George and Clifford (1996), training professionals in the retrieval mnemonics improved the resulting interviews in the current experiment, which extends the benefit of the MCI to French-language countries and to military police forces practicing within inquisitor justice systems.…”
Section: Discussionsupporting
confidence: 78%
“…Previous laboratory research found that these two mnemonics do not increase the amount of correct details recalled (e.g., Boon & Noon, 1994;Milne & Bull, 2002;Py, Ginet, Demarchi, & Ansanay-Alex, 2001) and, therefore, that this shorten version is as effective (e.g., Bensi, Nori, Gambetti, & Giusberti, 2011;Colomb & Ginet, 2012). This recently suggested instruction, which can be used to initiate a second free recall phase when appropriate (e.g., when police are at the beginning of a procedure and want exhaustive recall), was shown to elicit significantly more correct information during a second recall attempt than the change temporal order and the change perspective considered as a whole and also used to complete a first free recall (Colomb & Ginet, 2012). Several social and communicative components of the ECI (e.g., rapport building and transfer control) were also included in the MCI used here, as well as a sequenced and focused recall instruction (i.e., the witness must divide the event into several sequences, communicate them to the interviewer, and focus detailed retrieval on each sequence on its own).…”
Section: From the Cognitive Interview To The Modified Versions: A Hismentioning
confidence: 89%
See 2 more Smart Citations
“…3. A variation of this instruction was recently tested: the guided peripheral focus instruction (Colomb & Ginet, 2011). 4.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%